RISK ASSESSMENT DESIGN FOR PAYMENT FINANCIAL TECHNOLOGY COMPANY - HAQ AL FARISI NIM: 18214018 , MAHBUB
This thesis report aims to describe the risk assessment design and risk assessment tool design for payment financial technology companies. Background of this thesis is the requirement of payment financial technology companies to conduct risk management in order to fulfill Bank Indonesia rules, while a lot of financial technology companies still have status as startup companies so they tend to focus on business development and not focus on risk management. The development of risk assessment design in this thesis uses the Design Science Research Framework and equipped with Structured What-If Technique (SWIFT) to identify and analyze the impact of risk by referring to ISO 31000 and ISO 31010 documents. Meanwhile, the risk assessment design and the risk assessment tool design evaluation used in this thesis are Streamlined Cognitive Walkthrough and Black Box Testing. Designing a risk assessment using SWIFT techniques is divided into three main stages, namely risk identification, risk analysis, and risk evaluation. Risk identification and analysis in financial technology companies can be done using the SWIFT form. This form can help companies to identify risks and define risk impacts using a list of possible scenarios. While risk evaluation is conducted by giving an impact value, probability value, risk value, and mapping the risk value using a probability/impact matrix. The final result of this thesis is a risk assessment artifact equipped with a risk assessment tool that makes the companies can fill out SWIFT forms easier with a simple interface. The risk assessment tool can also automatically provide risk values based on the impact value and probability value so that it can reduce the risk assessment time.